Pelatihan Pembuatan Herbisida Formula Unihaz di Kebun Kelulut Desa Sangatta Selatan - Rahmatriananda Faradilla; Tri Agustin; Nauval Rafiq Izzudin; Novi Angelina Sundah; Destia Amandha; Stephanie Elfriede Ginting; Andrew Christianto Salusu; Ega Dyah Puspita Sari; Dwi Reza Ariyadi; Abdullah Arkananta Rasendrya Hasan; Ardhifa Firdaus (Jurnal Pengabdian Kepada Masyarakat, 2025)
Farmers in South Sangatta Village face serious challenges in controlling the growth of nutsedge, which is difficult to eradicate using conventional methods and requires the use of expensive chemical herbicides. This situation has prompted the development of alternative solutions through the development of more environmentally friendly, natural herbicides. Community service by students from the Community Service Program (KKN) was carried out in the form of training in the manufacture of Unihaz herbicide formulas in a stingless bean plantation in South Sangatta Village to address these issues. The methods used included training, demonstrations, and hands-on practice in making Unihaz herbicide formulas. This training has proven to provide an effective and economical solution while reducing farmers' dependence on expensive chemical herbicides. This is crucial for helping farmers become more independent and realizing a sustainable and environmentally friendly agricultural system.